A comparison of economic complexity in Türkiye and OECD countries: new data based on industrial products - Huseyni, Ibrahim; Inan, Serdar; Celik, Ali Kemal; Isleyen, Sakir (Emerald Group Publishing Ltd, 2025)
PurposeThis study aims to analyse T & uuml;rkiye's industrial economic complexity index (ECI-IND) for comparison with the ECI-INDs of member countries of the Organization for Economic Co-operation and Development (OECD). It also explores the causal relationship between economic complexity and economic growth in T & uuml;rkiye.Design/methodology/approachEmpirical analysis was directed at industrial export baskets consisting of 760 product groups distributed by 130 countries. These data were used to calculate the product complexity index (PCI) and ECI-IND values of these countries. The calculations then served as the basis for examining T & uuml;rkiye's economic complexity in comparison with that of OECD countries. Finally, the short- and long-term relationships between the ECI-IND and GDP per capita in T & uuml;rkiye were investigated using a time series analysis.FindingsThis study's findings revealed that T & uuml;rkiye ranked last in terms of economic complexity. The time series analysis showed unidirectional causality between T & uuml;rkiye's ECI-IND and its economic growth.Practical implicationsT & uuml;rkiye should concentrate on ensuring the convergence of its ECI with those of developed countries. Based on the existing literature, it is important for T & uuml;rkiye to implement policies that (1) increase human capital, (2) expand the share of R&D expenditures out of the GDP and (3) attract foreign direct investments, which advance technology transfer.Originality/valueThis study inquired into the ECI based on industrial products in T & uuml;rkiye and accordingly provided new data on countries. It also compared T & uuml;rkiye and OECD nations with respect to this index.
Keywords: Economic complexity index; Economic growth; Product complexity index; Industrial product